PEREMPUAN PELESTARI DAS, PEREMPUAN BERDA (Merintis Keberdayaan Pelajar Melakukan Pemberdayaan Perempuan Bersendikan Kearifan Lokal Sesuai Kurikulum 2013) - Damanik, Fritz Hotman S. (Bumi Lestari; Vol 14 No 2 (2014), 2016)
In Indonesia, there are 5.590 main rivers, 65.017 tributaries, and 500 lakes (Status Lingkungan Hidup Indonesia, 2010). Ironically, the rivers’ surroundings and watershed have faced enormous pressure since years ago because of they became the center of the development of civilization as well as the center of communities’ social-economic activities. Furthermore, the analysis to 40 watersheds in West Java indicated the decline of hydrological functions. 14 watersheds can be categorized as extremely critical, while 8 watersheds considered to be critical. The same situations are believed to occur all across Indonesia. The Basic Competence of Sociology for Social Sciences Specialization in High School, contained the demand for students to able to design, implement, and report community development action by using local wisdoms as foundation in the globalization era. From this basic competence, it is so appropriate to try to formulate an empowerment action for women as watershed conservationist, with high scholl students as facilitators. Why womesn ? The answers mostly related to gender stereotypes associated to women, such as gentle, sensitive, patient, and full of considerations. The stereotypes  will enable women to conservate as well as using the environment continuously. Or by other words, women are assumed to have the ability to improve welfare without ruin nature.
Keywords: empowerment, women, local wisdom, 2013 Curriculum